Challenges and opportunities in community pharmacists' identification and management of dry eye disease: a qualitative study. - Ng, Shong Li; Tey, Adrian; Sellappans, Renukha; Aftab, Raja Ahsan; Leong, Yat Yin; Yau, Mei Qian; Tan, Bee Kim (International Journal of Pharmacy Practice, 2025)
Objective To explore Malaysian community pharmacists' (CP) challenges in identifying and managing dry eye disease (DED) and opportunities to optimize DED care, as previous studies reported inconsistencies in DED identification by community pharmacy staff, and few publications describe Malaysian CP views on DED management in community pharmacy settings. Method Using the Social Ecological Theory for Community Health Promotion, individual in-depth interviews were conducted (May–June 2023) with 20 CP in Malaysia's Klang Valley. Participants with diverse DED management experiences were recruited using purposive and snowball sampling until data saturation. Interviews were audio-recorded, transcribed, independently coded by two researchers, and thematically analysed. Key findings CP faced 12 challenges in identifying and managing DED: patient-related (brand rigidity, 'quick fix' attitude, inadequate health literacy, and self-efficacy skills), provider-related (imprecise assessment, referral difficulties, knowledge gaps), therapeutics-related (short shelf life, affordability), and pharmacy-related (limited manpower, inadequate private consultation space, low eye health visibility). The 12 opportunities for optimizing DED care were community-related (eye health education, holistic approaches, public awareness), profession-related (decision-support mobile health applications integrated with evidence-based DED management protocols to streamline consultation processes, interdisciplinary collaborations), industry-related (pharmaceutical and medical device advancements, comparative data on medication value, promotion of proactive management), and organization-related (management-mandated resource allocation, ancillary staff education, and expanded products and services). Conclusion Malaysian CP encountered challenges in identifying and managing DED. Knowledge sharing and collaborations with ophthalmologists improve DED management by CP, while clinicians can stay updated on medication-related recommendations and treatment adherence. The role of digital health in these processes requires further study.